A Comparative Analysis of Prefabricated and Traditional Construction of a Rail Transit Equipment Room Piping System Under a Mountainous Area: A Case Study of Chongqing Rail Transit - Wang C; He B; Li G; Wang J; Ou Y; Luo Q; Chen H; Zhong K; Liu Z; Zhou Y (MDPI AG (Basel, Switzerland), 2025)
Prefabricated technology addresses inefficiencies and quality variations in traditional construction but exhibits insufficient adaptability to pipeline systems in mountain rail transit equipment rooms (PPMRR), with obvious gaps in schedule and full-life-cycle economic quantification. This study aims to quantify the schedule and economic advantages of prefabrication for PPMRR and explore mountain-adapted implementation pathways. Taking Chongqing Rail Transit as the empirical context, this study employs case studies, field investigations, and semi-structured interviews as research methods. Results show that compared with the traditional mode, the prefabricated mode shortens the total project duration of PPMRR by 62–70% and reduces the 30-year full-life-cycle cost by 38.6%. This study addresses the research gap in schedule–economic quantification for the prefabricated mode of pipeline systems in mountain rail transit equipment rooms. It can provide critical references for construction planning, cost management and control, and the formulation of local prefabrication technical standards for mountain rail transit projects, thereby promoting the scalable application of prefabricated technology in complex terrain infrastructure.
Keywords: prefabricated mode; Mountain city; Chongqing; rail transit; pipeline system